Age determination of the Indian whiting, Sillago indica using otolith ring count - David, Anuradha; Pancharatna, Katti (Indian Journal of Fisheries, 2011)
Using length-weight relationship and otolith dimensions, an attempt was made to estimate the age of Sillago indica (n = 175) from Karwar Bay. Length-weight relationship was established using power equation (W = aLb). Condition factor (K) and relative condition factor (Kn) were calculated for each fish using the formulae K = W x 105 /L3 and Kn = W/w respectively. Otolith dimensions such as diameter (OD), weight (OW) and growth ring count (ORC) were recorded from sagittae. The results revealed that length-weight relationship follows cube law thus, W = -3.74 L 2.46 suggesting the isometric pattern of growth of this fish. K and Kn increased up to 190 mm (when otoliths showed 3 growth rings) and then decreased giving a clue about the size and age of attainment of sexual maturity in this fish. Otoliths obtained from different sized fishes revealed the presence of 1-5 growth rings. Further, ORC, OW and OD showed a positive correlation with fork length (FL) and total weight (TW). Likewise, FL and TW also showed a linear correlation.